Importance of compliance technologies in marketing - Subhajit Chakraborty (International Journal of Technology for Business (IJTB), 2020)
Every organization conducting business activities is familiar with the scientometric approach of the term "compliance". As we all consider that human beings are made of blood and flesh, in such a way business enterprises are embedded with compliance and regulations. The concept of compliance strives to express that business enterprises make ceaseless endeavours to adhere to the local and foreign laws, rules and regulations pertaining to its activities, including corporate and internal policies, in order to achieve compliance competency as per international standards. For many years India witnessed enactment of various anti-corruption legislations, the concept of compliance has gained more significance in various industries and companies which are indulged in share trading, investment business, health care and financial services. However with the launching of various anti-corruption legal frameworks, industries were run in an uncompromisingly rigid manner and as such for any compliance and legal division there was a need for strict monitoring of the compliance programs by industrial enterprises which were required to confront with numerous laws and regulations. It is by means of compliance competency and regulations that business enterprise can prosper and go great guns, provided it is well-conditioned and nurtured by an ethical environment and proper governance. The paper will discuss how compliance technologies have impacted the marketing activities of business enterprises.
Keywords: 650; Compliance; Competence; Technologies; Marketing; Enterprises